Small profits mean peace: food price, risk aversion, and farmers’ choices of sale channels - Tan Tian; Yuan Yuan Su; Pei Chen (Frontiers in Sustainable Food Systems)
Most farmers in China show an strange attitude towards food sale channels:they prefer low priced channel rather than high priced channel. This paper examines the mechanism by which food price affect farmers’ choices of sale channels and the role played by risk aversion, based on the 2022 China Land Economic Survey. The results indicate that higher prices are more likely to lead farmers to choose dealers who are private buyers offering flexible terms, compared with depots which are government procurement centers ensuring stable prices and other channels. It reveals that the underlying reason for farmers’ choices is the certainty effect, which causes farmers to prefer dealers offering certain profits over depots with uncertain profits, despite the high prices. It is further found that risk aversion has a mediating effect on the relationship between food price and farmers’ choices of sale channels.